Penguatan Literasi Kelautan Berdasarkan Kerangka NOAA untuk Taruna SMK Pelayaran Tayu Kelas X - Dewi Amaliya; Nigita Ariyani (PPPM Polimarin, 2025)
Ocean literacy is an essential competence for students in maritime vocational schools, considering the strategic role of the ocean in human life and sustainable development. This study aims to examine the strengthening of ocean literacy among Grade X Pelayaran Tayu vocational high school students through instruction based on the National Oceanic and Atmospheric Administration (NOAA) Ocean Literacy Framework. The study employed a quasi-experimental approach using a one-group pretest–posttest design. The participants were Grade X students from a maritime vocational high school. Data were collected using an ocean literacy test and an attitude questionnaire, and analyzed through descriptive and inferential statistical techniques. The findings indicate that instruction grounded in the NOAA Ocean Literacy Framework enhances students’ overall ocean literacy and fosters more positive attitudes toward ocean conservation. These results suggest that the NOAA Ocean Literacy Framework can be effectively adapted to vocational education contexts and contributes to the development of contextual and sustainable ocean education.